Sainsmatika-based story tale book to improve environmental awareness of 4th grades students - Muhammad Nur Wangid (Jurnal Inovasi Pendidikan IPA, 2018)
This study aimed to determine the effectiveness of sainsmatika-based storybooks to improve environmental awareness for students. The experimental research design was used in this study, which involved two classes, namely the control class and the experimental class. Each class consisted of 30 students. The research subjects were 60 students of grade 4 students consisting of 36 female students and 24 male students. The analysis process used an independent t-sample test to find out the differences in each outcome. The results showed that based on the gain value obtained, it found out that the average value of the pre-test results in the control class was 49.47 and the posttest result was 67.41. This showed that the increasing score in the pre-test and post-test control classes only reached 2.34 which can be classified as low. Whereas in the experimental class, the results showed that the average pre-test results in the experimental class was 52.63, and the post-test results were 78.90. It means that the students' environmental awareness on pre-test and post-test results were 3.48, which was in the medium category. The results of the experimental research showed that the use of sainsmatika-based storybooks has a significant impact on students' environmental awareness. The results of hypothesis testing on environmental awareness variables showed that there were significant differences between the control group and the experimental group. The experimental group was better than the control group (t count 3.124 at level p 0.01).